PENGARUH DANA DESA TERHADAP KETAHANAN PANGAN: STUDI KASUS DI KABUPATEN SLEMAN TAHUN 2024 - Alza Nashuha Shahhira; Windy Setianingrum; Shabrina Hanun (Badan Perencanaan Pembangunan Daerah Kabupaten Sleman, 2025)
Food security is a complex issue at various levels, from global to regional. Sleman Regency is experiencing increased agricultural land conversion, which could reduce local food production capacity. The allocation of Village Funds through the Village Cash for Work Program (PKT) is one of the efforts to overcome this problem. This study aims to analyze the effect of Village Funds on the level of food security in Sleman Regency in 2024. This study uses data from the Food Security and Vulnerability Atlas (FSVA) from the Badan Pangan Nasional dan data Potensi Desa (PODES) from the Badan Pusat Statistik (BPS). The analysis was conducted using the ordered logit method because the dependent variable was categorical, namely the village food security index ranking. This model identifies factors that influence food security status. The results show that Village Funds have a significant effect in improving food security in villages categorized as “moderately vulnerable” and “moderately resilient”, reflecting the important role of Village Funds in the food security transition phase. However, the impact begins to decline in villages with relatively high food security levels, where additional public investment no longer increases output proportionally. These findings emphasize the importance of a policy framework that supports the optimization of Village Funds for productive activities and basic infrastructure development, including improving farmers' capabilities, strengthening institutions, and providing supporting facilities that can expand community access to food in a sustainable manner.